The Influence of Location and Selling Price on Purchasing Decisions at PT. Gapura Prima Group - Iis Noviyanti; Feb Amni Hayati (PINISI Discretion Review, 2019)
Today's economic development is marked by the emergence of various forms of the property very quickly and continuously. This study aims to determine the effect of location and selling price on the purchasing decision of Bailey's City Ciputat Apartment Unit at PT. Gapura Prima Group. The method used was explanatory research with a sample of 86 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study location have a significant effect on purchasing decisions of 42.0%, the hypothesis test obtained significance of 0,000 <0.05. The selling price has a significant effect on the purchase decision of 46.9%, the hypothesis test obtained a significance of 0,000 <0.05. Location and selling price simultaneously have a significant effect on the purchase decision of Bailey's City Ciputat Apartment Unit by 56.2%, the hypothesis test obtained significance of 0,000 <0.05.